2017
DOI: 10.5704/moj.1703.019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antibiotic Cement Coated Nailing in Infected Nonunion of Tibia

Abstract: IntroductionInfected nonunion of long bones is a chronic and debilitating disorder. It is more difficult to deal with when the implant used for internal fixation itself becomes a potential media for infection because of bacterial adhesion and biofilm formation. Traditionally, it is managed by two-stage procedure for controlling the infection first and then treating the nonunion. This study has been undertaken to explore antibiotic cement coated nailing as single stage treatment modality for treating infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Antibiotic-coated hip spacer for periprosthetic infection treatment are described in detail in the literature [2] , [4] , [5] , [7] , [8] , [10] , [12] , [20] , [21] , as well as the use of antibiotic-coated intramedullary nails for infected long bones fractures or infected nonunions [13] , [14] , [16] , [17] , [22] , [23] . However, there are few reports describing therapeutic options applied to cases in which a deficit of proximal bone stock of the femur coexist with a femur shaft defect (fracture or nonunion) in the context of an infection; most of them were case reports about a single and unique salvage technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic-coated hip spacer for periprosthetic infection treatment are described in detail in the literature [2] , [4] , [5] , [7] , [8] , [10] , [12] , [20] , [21] , as well as the use of antibiotic-coated intramedullary nails for infected long bones fractures or infected nonunions [13] , [14] , [16] , [17] , [22] , [23] . However, there are few reports describing therapeutic options applied to cases in which a deficit of proximal bone stock of the femur coexist with a femur shaft defect (fracture or nonunion) in the context of an infection; most of them were case reports about a single and unique salvage technique.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the implantation of the antibiotic cement-coated intramedullary nails used for the treatment of osteomyelitis associated with fractures or infected nonunions of long bones [13] , [14] , [17] . This technique allows intramedullary debridement (through reaming, intramedullary irrigation, and debris removal), provides both fracture stability and high local concentration of antibiotics, and restores limb function by maintaining joint mobility and allowing weight-bearing ambulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thonse and Conway reported an 85% rate of infection control [ 6 ]. Bhatia et al reported a 95% rate of infection eradication [ 37 ]. Similar results proved that the bone cement nail has a satisfactory infection control effect [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of bone union, there are different results in different studies. Bhatia et al reported a 60% rate of bone union without an additional procedure [ 37 ]. Zheng and Hang reported a 22% rate of union [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are cumbersome and may take several months to regenerate bone. Such infected non-unions should preferably be managed with staged surgeries where the intramedullary and local infection is controlled with local and intramedullary antibiotic cement spacers and temporary stabilization with an external fixator [ 4 ]. Additionally, prolonged antibiotic therapy is required according to the culture reports.…”
Section: Introductionmentioning
confidence: 99%